Design and construction of an optical reflectometer for research on spin crossover materials - Sucre, Oscar Elías; D”™Onofrio, Lisseta; Constant, Héctor (Ciencia, 1970)
An optical reflectometer instrument has been design and constructed for research on Spin Crossover Materials, a new kind of compounds which promises to be very significant in molecular memory systems. By using the reflectivity as a physical parameter to investigate the magnetic state of a material, this instrument shows its capability of performing studies of magnetic hysteresis. It mainly consists of a Y-shaped optical fiber, a light source, a sample holder and two optical setups for sampling the reference and reflected signals. Several technical aspects are discussed, like the AC noise electronic filtering, the baseline adjustment, the temperature control, and the remote control of the instruments by GPIB control interface over a virtual instrument platform (LabVIEW®). Measurements of the reflectivity can be performed as a function of temperature from 300 K down to 30 K in a closed cycle cryostat.